Development of a highly sensitive Gaussia luciferase immunoprecipitation assay for the detection of antibodies against African swine fever virus - Ding, Jingjing; Yang, Jifei; Jiang, Daoyuan; Zhou, Yanyang; Li, Chenxi; Li, Yanhua (Frontiers in Cellular and Infection Microbiology, 2022)
In recent years, African swine fever (ASF) has caused a devastating blow to the swine industry globally. Since no effective vaccine is available, strict biosafety measures and rapid diagnosis are the most effective strategies for ASF control. ASFV p30 is one of the most antigenic viral proteins that have been widely used in the field for serological diagnosis of ASF infection. In this study, we developed a luciferase immunoprecipitation system (LIPS) assay for the detection of ASFV antibodies in pig serum using Gaussia luciferase (GLuc)-tagged p30 as a diagnostic antigen. The optimal GLuc-p30 input of 107 luminance units (LU) and optimal serum dilution factor of 1/100 were set to achieve the highest P/N ratio. Based on 87 ASFV-positive and negative pig sera, the cutoff value of the S/N ratio could be set between 2.298 and 30.59 to achieve 100% sensitivity and 100% specificity. Moreover, the diagnostic sensitivity of this LIPS is comparable to that of a commercial enzyme-linked immunosorbent assay (ELISA) and the specificity of LIPS is even superior to the tested ELISA. In conclusion, we have established a LIPS assay for ASFV antibody detection, which could be a potential method for ASFV diagnosis in laboratories and farms.